Three strikes for Rotten Ralph - Gantos, Jack (Farrar Straus Giroux, 2011)
When Rotten Ralph, the cat, fails to win a spot on a baseball team with his friend Sarah, he becomes the "cat boy" instead, still dreaming of proving himself the superstar he imagines himself to be.